Study of Ethiopian genetically modified and organic cotton fiber quality compared with conventional cotton - Chirato Godana Korra; Kura Alemayehu Beyene; Tiliksew Addis Desta (Cogent Food & Agriculture)
In Ethiopia, investigation of fiber quality and commercialization is limited to conventional cotton and there is no fiber property analysis for Organic and genetically modified cotton. The objective of this study is to characterize organic and genetically modified cotton and compare them to conventional cotton varieties. Conventional varieties with chemically treated and untreated seed cotton; organic and genetically modified cotton samples were collected using random sampling methods from different regions of Ethiopia. Cotton fiber qualities are tested on High-Volume Instruments based on the ASTM standard. The tested data is experimentally designed and analyzed using SPSS software version 22. The model is significant for the effect of fiber quality parameters on the similar and different cotton varieties p < 0.05. The JKCH 1947 cotton has a maximum spinning consistency index, Uniformity index, and maturity ratio of 151, 86.6, and 0.83, respectively. The organic cotton cultivated MRC (270) has a maximum fiber strength of 29.29 g/tex and elongation of 7.44 mm, minimum short fiber content of 4, and maturity of 4. Deltapine (DP) 90 untreated seed Forgena cotton has a maximum micronaire value of 4.24 and a minimum fiber length of 27.17 mm. Acala SJ2 cotton variety has a maximum fiber length of 28.3 mm, minimum micronaire of 3.69, and elongation of 4.44 mm. It was revealed there is little improvement in qualities of the organic and genetically modified cotton. Chemical treatment has a significant effect on the quality of cotton. Cotton parameters have a significant effect on varieties with strong and weak correlations.